The India Healthcare Sector: Governance and Managerial Challenges - Ramani, K. V. (Advances in Social Sciences Research Journal, 2014)
The global health care industry estimated at 5 trillion, is one of the world’s largest and fastest-growing industries. India’s healthcare industry which is expected to be around 45 billion by the end of 2013 accounts for less than 1 % of the global healthcare industry, but has to address the healthcare needs of 17 % of the global population. The India health sector therefore faces severe resource constraints to deliver health services. India spends about 5 % of GDP on healthcare compared with 10-12 % of GDP on healthcare spending by developed countries. The government’s share in the total healthcare expenditure in India has remained around 1 % of GDP, and therefore the private sector has become a dominant player in health service delivery. Regulation of the private sector is essential for successful Public private Partnership. The unregulated private healthcare sector also raises serious concerns regarding the accountability, equity and quality of service delivery. India ranks 112 out of 193 WHO countries on health system performance. The WHO Report on Macroeconomics and Health [Jeffery Sachs, et al 2001], followed by the Report of the National Commission on Macroeconomics and Health [GoI, August 2005] provide strategic directions to improve our health system performance. Improvements in our health system performance call for a significant scaling up of resources by the Government of India, and tackling the non-financial obstacles that have limited the capacity to deliver health services. Building health systems that are responsive to client needs requires politically difficult and administratively demanding choices. Keywords: Healthcare, Management Challenges, India